The Reality of Logistics Services Performance in the Algeria A Reading in The Light of (LPI) for The Period (2007 - 2022) - boussadia, mourad; ALIOUA, ALI (Journal of Research in Finance and Accounting, 2024)
This study aimed to diagnose and analyze the reality of logistics services performance in Algeria during the period (2007-2022), and to achieve this purpose The World Bank Logistics Performance Index (LPI) and the sub-indices which falls within it (CUST, INFR, ITRN, LOGS, TIME, TRAC) were relied upon. The study concluded that despite the noticeable relative improvement of the overall index (LPI) throughout the study period, the analysis of the sub-indices showed that the quality of performance of logistics services in Algeria did not reach the required level, and was below the global average, which puts the relevant authorities in front of great challenges require additional efforts to overcome performance obstacles and find appropriate solutions to enhance the competitiveness of Algerian logistics services in international markets.